10.C. Round table: European public health week: how to unite a continent to celebrate healthy populations. (30th September 2020) - ,; ,
Abstract: The first two editions of the European Public Health Week (EUPHW) took place in May 2019 and May 2020. Both exceeded all expectations, registering more than 140 events in more than 30 countries each year - despite the pandemic context and a fully online format in 2020. In this session we will share insights from both editions, with the round table format allowing for a wider discussion of experiences with other countries from around the world. Under the motto "celebrating healthy populations" in 2019 and "joining forces for healthier populations" in 2020, EUPHW aims to raise awareness about public health, maximise existing messages around the five themes that are set each year, and encourage collaboration among all professionals contributing to public health at local, national, regional and European level. Amid the COVID-19 public health emergency, the importance of ensuring that populations remain healthy and that the public health community joins forces gained momentum. The five days of the 2020 edition were dedicated to the Sustainable Development Goals, primary care in the digital age, staying together for mental health, equal health for all, and healthy ageing - under the exceptional overarching theme of 'COVID-19 Collaboration, Coordination, Communication'. Last year's edition covered physical activity, healthy environments, the healthcare workforce, healthy and sustainable diets, and youth mental health. The EUPHW Coordinator will explain what the initiative consists of and reveal key figures from both editions. The different types of involvement in the EUPHW will also be described: Event host, Disseminator and Participant. Three panelists will represent the EUPHW Steering Committee, providing important insights into the backstage preparation of this large-scale initiative. One is the communications coordinator of the EUPHAnxt network, representing contributions from the young generation of public health professionals in Europe. A second panelist will not only share the experience of hosting EUPHW events but also represent EUPHA Sections, which play an important role in fact-checking resources and messages about each of the annual themes. The fourth panelist will share their experiences at country level through the Austrian Public Health Association and its own National Public Health Week. The final panelist will share examples of activities hosted by the community of public health schools across Europe. Although the focus of the EUPHW is the European region, its online reach enables the participation from anywhere in the world. In fact, both editions saw registered activities in Brazil, USA, South Africa, Kenya, Australia and Colombia. The EUPHW is an initiative by the European Public Health Association (EUPHA), receives co-funding under an operating grant from the European Union's Health Programme (2014-2020) and is supported by the WHO Regional Office for Europe. Key messages: The European Public Health Week brings together a continent to raise awareness about important public health issues. The workshop unveils how public health themes are explored on different contexts, across different cultures and in different formats. Panelists: Debora Miranda EUPHA, Portugal Contact: debbiemiranda@gmail.com Thomas Dorner Austrian Public Health Association, Austria Contact: thomas.dorner@meduniwien.ac.at Nicole Rosenkötter NRW Centre for Health - Health Information, Germany Contact: Nicole.Rosenkoetter@lzg.nrw.de Pasquale Cacciatore EUPHAnxt, Italy Contact: pasqualecacciatore@gmail.com Robert Otok AASPHER, Belgium Contact: robert.otok@aspher.org